Digital Literacy-Based Health Promotion at Posyandu Banjar Teges Kanginan - Sutrisna, I Putu Gede; Nuryanto, Kadek; Damayanti, Ida Ayu Manik (Jurnal Abdimas ITEKES, 2021)
The lack of posyandu cadres who have expertise in health sciences causes the health promotion process to be less effective. This is because human resources do not have the knowledge and skills in health promotion. In addition, the cadres of the Banjar Teges Kanginan Posyandu, Peliatan Village have never received training on COVID-19 prevention. The media used in health promotion also tend to be monotonous, only using loudspeakers which are used for socialization around the Teges Kanginan Traditional Village. This shows that the process of health promotion takes place in a monotonous and less innovative way. Based on the description above, there are two problems that will be given a solution, namely the knowledge aspect of digital literacy-based health promotion and the skill aspect of digital-based health promotion. The solutions given related to the above problems are providing training and assistance in making health promotion media based on digital literacy, communication and public speaking, using and how to make hand sanitizers and disinfectants, training and mentoring on how to wash hands properly and correctly. The output target in the implementation of this devotion to the community is that the cadres of the Banjar Posyandu Teges Kanginan have the knowledge and skills of digital literacy-based health promotion. The results of this activities is implementation are as follows. (1) There is an increase in the knowledge of posyandu cadres related to digital literacy-based Health promotion. (2) there is an increase in the skills of posyandu cadres about conducting clean and healthy lifestyle, especially making handsanitizers. The high interest of posyandu cadres in improving public health, especially using health promotion based on digital literacy, it is necessary to hold further training and coaching related to the implementation of digital literacy in promoting public health